PENGARUH PENGGUNAAN TEPUNG KELADI (Colocasia Esculenta) SEBAGAI PENGGANTI TAPIOKA TERHADAP KUALITAS ORGANOLEPTIK SOSIS BABI 1 (The effect of using taro flour (colocasia esculenta) as substitution of tapioca on organoleptics quality of pork sausage) - Sarisando Mbinu Peka; Gemini Malelak; Pieter Rihi Kale (JURNAL NUKLEUS PETERNAKAN, 2021)
The purpose of this study was to determine the effect of using flour taro as a substitution of tapioca on organoleptic quality of cooked pork sausage. Completely Randomized Design (CRD) with four treatments and three replications was used in this experiment. The treatment consisted of TK0 = without addition of taro flour (Control), TK50 = Use of tapioca flour 50% + flour 50%, TK75 = Use of tapioca flour 25% + flour 75%, and TK100 = Flour 100% (tapioca 0 %). The results showed that using of flour taro was highly significant (P<0.01) influenced the color, aroma and taste of pork sausage. As the taro flour increased, the color of sausage changed to brown, reduced the aroma and taste of sausage. To sum up, using taro flour 50%-100% as a substitution of tapioca flour causes the sausage become browner; reduce aroma and taste.